Architectural scale models in the digital age design, representation and manufacturing - Stavriâc, Milena; Si¯danin, Predrag; Tepavæcevic§, Bojan (Wien Springer, 2013)
A major challenge in the age of advanced digital technology and parametric design in architecture is making physical models of complex geometric shapes and their multiple structural connections. This approach requires new modeling strategies, technology and methods which are covered in this book. Complex geometric forms generated using virtual media can be tested and validated only by means of physical models, and so can their practical application be controlled. The complexity of contemporary architectural design bids the mastery of new methods of producing scale models, which opens a new chapter in the field of modeling, and which is the focus of this book. Along with the traditional methods forming a basis for modeling, this book presents the principles of digital NURBS modeling, parametric modeling, digital support to modeling, and model manufacturing, complete with a number of tutorials, practical advice and examples found in architectural practice today.--Source other than Library of Congress.
Keywords: Architectural models -- Computer-aided design